Asuhan Kebidanan Continuty Of Care (Coc) pada NY “I” Umur 22 Tahun dengan Normal - Arsfandi, Asraria; Hapsari Windayanti (Universitas Ngudi Waluyo, 2023)
Continuity of Care (COC) midwifery care is continuous midwifery care provided to mothers and babies starting during pregnancy, childbirth, newborns, postpartum and family planning. COC midwifery care is one effort to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) (Diana, 2017). Based on the description above, the author monitored Mrs. I am pregnant, giving birth, postpartum, neonate and family planning at the Dharma Wahyu Agung Clinic. Because the clinic has met midwifery care standards and has an MOU with educational institutions based on Decree of the Minister of Health of the Republic of Indonesia No. 938/MENKES/SK/VIII/2007. Regulation of the Minister of Health of the Republic of Indonesia No. 1464/MENKES/PER/X/ 2010 concerning licensing and implementation of midwife practice. So the author is interested in carrying out midwifery care entitled